2010
DOI: 10.1177/1052562910374878
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Management in the Slovak Republic: Lessons Learned and Encouragement for Potential Fulbright Scholars

Abstract: This story of a Fulbright scholar's experience is designed to help future Fulbrighters and those interested in teaching in more culturally diverse environments. Although each Fulbright teaching experience is unique, the majority of challenging situations can be resolved by adequate preparation before the assignment and by the willingness to be flexible once abroad. This article provides guidance for those contemplating applying for a Fulbright, preparing to teach abroad, living and teaching in another culture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The years of service were separated into 5-year increments on the survey. Due to the competitive nature of the program, many faculty don't apply for a scholarship until they are well-established in their career, which is usually after they have been teaching for 10 or more years (Hall, 2007;Garson, 2005;Meyer-Emerick, 2010). Consequently, due to the low response rate of faculty with 1 to 15 years, the years of service were divided into two categories, 1-20 years and 21 or more years.…”
Section: How International Experience Affects Teaching: Empirical Resmentioning
confidence: 99%
See 3 more Smart Citations
“…The years of service were separated into 5-year increments on the survey. Due to the competitive nature of the program, many faculty don't apply for a scholarship until they are well-established in their career, which is usually after they have been teaching for 10 or more years (Hall, 2007;Garson, 2005;Meyer-Emerick, 2010). Consequently, due to the low response rate of faculty with 1 to 15 years, the years of service were divided into two categories, 1-20 years and 21 or more years.…”
Section: How International Experience Affects Teaching: Empirical Resmentioning
confidence: 99%
“…These exchange or study abroad programs will enrich a faculty's understanding or perspective of a country and it can have a positive impact on the globalization of a professor's teaching as well as improving research contacts and collaboration (Garson, 2005;Meyer-Emerick, 2010). A program that provides an excellent opportunity for teaching and research abroad is the Fulbright Scholar Program.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated a relationship between the U.S. Fulbright Scholar Program and changes in academics’ research and professional networks (Demir et al, 2000; Eddy, 2014; Meyer-Emerick, 2010; Pope et al, 2017). These studies have mainly employed qualitative methodologies reporting on personal experience or the experiences of a small group of academics.…”
Section: Study Contextmentioning
confidence: 99%